2020
DOI: 10.4012/dmj.2019-061
|View full text |Cite
|
Sign up to set email alerts
|

Acidity-induced release of zinc ion from BioUnion<sup>TM</sup> filler and its inhibitory effects against <i>Streptococcus mutans </i>

Abstract: BioUnion filler incorporated into restorative/coating materials is a new bio-functional glass powder. The most unique function of BioUnion filler is its ability to release Zn 2+ in acidic environments. In this study, the ion release profile of BioUnion filler under acidic conditions and its antibacterial effects against Streptococcus mutans were evaluated. The concentrations of Zn 2+ released from BioUnion fillers into acetic acids were greater than those released into water. S. mutans inhibition by BioUnion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…Zn 2+ is known to exhibit antibacterial effects against oral bacteria 37,46) . The MIC/MBC values of zinc against S. mutans were reported to be lower than those of fluoride 6) . Interestingly, Liu et al 6) reported that BioUnion fillers demonstrated accelerated release of Zn 2+ under acidic conditions and exerted strong bactericidal or inhibitory effects against oral bacteria.…”
Section: Ion-releasing Glass Fillers: Multiple Ions-releasing Typementioning
confidence: 96%
See 4 more Smart Citations
“…Zn 2+ is known to exhibit antibacterial effects against oral bacteria 37,46) . The MIC/MBC values of zinc against S. mutans were reported to be lower than those of fluoride 6) . Interestingly, Liu et al 6) reported that BioUnion fillers demonstrated accelerated release of Zn 2+ under acidic conditions and exerted strong bactericidal or inhibitory effects against oral bacteria.…”
Section: Ion-releasing Glass Fillers: Multiple Ions-releasing Typementioning
confidence: 96%
“…Therefore, other antibacterial nanoparticles have been used as fillers for resinous materials. Zinc oxide powders, incorporated as opaque reinforcing fillers in resin composites 36) , display antimicrobial properties by blocking the synthesis of bacterial cell walls 6,37) . Zinc acts directly by altering cell proteins via processes such as transmembrane proton translocation, or indirectly by inhibiting protease-induced bacterial adhesion [37][38][39] .…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations